Implementation of The Values of 6 Thobiat Luhur Informing Student's Moral and Character at As-Syifa Junior High School - Endarwan, Wildan Da,i Ichsan; Maksum, Muh. Nur Rochim (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: to explain what is 6 thobiat luhur and how they are implemented, as well as to see how effective the program is in developing the morals and character of students at As-Syifa Middle School. Methodology: This type of research is field research, a form of research conducted through surveys or observations at specific locations. This research approach uses a qualitative approach, which focuses on collecting data in the form of written and verbal information related to the attitudes or behavior of the individuals being observed, rather than through statistical data or numbers. This approach uses direct observation methods with Results: 6 thobiat luhur are Islamic character values relevant to facing the challenges of globalization, which impact students' morals and character. These values include honesty, trustworthiness,mujhid muzhid, harmony,unity,good cooperation. These six values not only shape personal character with integrity and responsibility but also strengthen social relationships between individuals within the school environment. The implementation of the 6 thobiat luhur at As-Syifa Middle School is carried out comprehensively, both within the boarding school environment and within the school's learning activities. The value of honesty is instilled through an honesty canteen and the implementation of strict sanctions for academic violations. A sense of trustworthiness is fostered by accustoming students to maintaining and caring for school facilities. The value of muzhid mujhid is implemented through the development of academic responsibility, time discipline, and financial management through the school bank program. Meanwhile, the values of harmony, unity, and cooperation are realized through the habituation of harmonious social interactions, deliberation in problem solving, group work in learning, and student participation in extracurricular activities and school organizations. Overall, the implementation of 6 thobiat luhur has proven effective in fostering morals, forming positive character, and creating a conducive, harmonious, and collaborative school environment.